PHOTOIONIZATION CROSS-SECTION AND RESONANCE STRUCTURE OF ATOMIC SULFUR - ALTUN, ZİKRİ (IOP PUBLISHING LTD, 1992)
Many-body perturbation theory has been applied to calculate the partial and total photoionization cross sections for neutral sulphur from the first ionization threshold at 10.36 eV to 60 eV. The excitations from the ground state S(3s(2)3p4 3p), leaving the residual S+ ions in the lowest five LS states (3s(2)3p3 4S, 2D , 2P and 3s3p4 4p, 2P), are considered. The results are presented in both the dipole length and velocity forms. The threshold behaviour of the partial photoionization cross sections are found to be dominated by the overlapping autoionizing resonances converging to S+(3s(2)3p3 4S, 2D, 2P) and S+(3s3p4 4p, 2p) limits. The excited single-particle states are calculated in an effective single-particle potential which includes, in an approximate way, the effects of the interaction among many final channels. The results are compared with the previous photoionization studies of sulphur.
Keywords: ANGULAR-DISTRIBUTIONS; PHOTO-IONIZATION; SULFUR